HUBUNGAN PENGETAHUAN DAN TINGKAT PENDIDIKAN TERHADAP PERILAKU CALON PENGANTIN UNTUK MELAKUKAN SKRINING PRANIKAH TRIPLE ELIMINASI DI PUSKESMAS IBRAHIM ADJIE KOTA BANDUNG TAHUN 2025 - barbara, Maria awaldina dua; Auziyati, Mufidha (SINERGI : Jurnal Riset Ilmiah, 2025)
Triple elimination premarital screening is an important step in early detection of infectious diseases such as HIV, syphilis, and hepatitis B to ensure their physical health before entering married life. However, the participation rate of prospective brides and grooms in this program is still low. In West Java Province, the achievement of health check coverage indicators for prospective brides and grooms was only 39.7% of the target of 80%. At the Ibraim Adjie Community Health Center in Bandung City, only 53 out of 203 people participated in screening in 2024. This low coverage indicates a significant challenge in increasing the participation of prospective brides and grooms in triple elimination checks, potentially related to a lack of knowledge and less supportive attitudes towards health screening for prospective brides and grooms. This study aims to determine the relationship between knowledge and education levels on the behavior of prospective brides and grooms to undergo triple elimination premarital screening at the Ibrahim Adjie Community Health Center in Bandung City in 2025. This study used a quantitative approach with a cross-sectional design. The sample consisted of 35 prospective brides and grooms in Cibangkong Village, the working area of the Ibrahim Adjie Community Health Center in 2025, using the total sampling technique.Data collection was conducted through a questionnaire that had been tested for validity and reliability. Data analysis used the Chi-Square test with a significance level of <0.05. The results of the study using the Chi-Square test showed results for knowledge (p = 0.000) and education level (p = 0.000). There was a significant relationship between knowledge and education level on the behavior of prospective brides and grooms in undergoing triple elimination premarital screening